Exploration of juvenile delinquency in grade X students at SMK X Kupang city - Rosemarry Selderika Anicha Malelak; Mernon Yerlinda Carlista Mage; Feronika Ratu (UKInstitute, 2024)
Juvenile delinquency is a problem that occurs in a deviant adolescent environment so that adolescents take actions that harm themselves, family, school and the environment. The purpose of this study was to explore forms of juvenile delinquency, factors of juvenile delinquency, the impact of juvenile delinquency, and school efforts in managing juvenile delinquency. Data collection techniques are observation and interviews. Data analysis techniques used Interpretative Phenomenological Analyisis (IPA). Referencial Adequacy Checks and Member Checks as techniques to strengthen data credibility. Sampling in this study used Purposive sampling technique with a total of 6 respondents. The results of this study show that the influence of juvenile delinquency is greater influenced by association with peers.